Women's Perception of the Quality of the Community's Role in Waste Management - Sholihah, Hidayatus; Kresnapratiwi, Rahajeng Galuh Imansari; Riniwati, Harsuko; Wike, Wike; Riskiyah, Faridatur; Wardana, Fitri Candra (Sekolah Pascasarjana Universitas Brawijaya, 2024)
Community participation in waste management is very important because the community contributes the largest volume of waste generation. The purpose of the study was to evaluate the quality of the community's role in waste management from the perspective of women's perceptions. Data were obtained from 30 female organization administrators in Dau District, Malang Regency. The data were analyzed by using the ratio between the facts of respondents' answers and the maximum score for the quality of roles with ordinal data scales. The results showed that group roles' quality was highest, discussion attendance was high, physical activity was high, and waste management fees were lowest. This research suggests that public awareness of paying dues needs to be increased by motivating through the 3R partial waste management results to improve public facilities in the village and sub-district areas. Keywords: decision-making, fact and ideal score ratio, role quality, waste management